Research of methods and modes of drying of gluten-free pasta - Dubkovetskyy, Igor; Yurchak, Vera; Rak, Valentina; Burlaka, Tatiana; Kazmiryshen, Vyacheslav (My University, 2019)
Application of thermo-radial-convective drying in the first drying period, and in the second period - convective drying promotes the obtaining of wheat and corn pasta of the best quality. The strength of wheat products is 3.7 N, and the rate of transition of dry substances to the cooking water - 10.7% to DM. The strength of gluten-free corn products is 3.5 N, dry matter transition - 13.9% to DM. This method also contributes to a reduction of energy consumption for the drying of wheat pasta by 1.1 times compared to the convective method for corn pasta by 1.35 times and is, respectively, 2.28 and 1.72 kW / kg of raw products. It is proved that the use of thethermo-radial-convective method in the first period of drying of gluten-free pasta, and in the second period of the convective method allows to reduce energy consumption by 1.5 times and to ensure good quality of products.
Keywords: gluten-free pasta; thermo-radiative drying; energy consumption; кафедра процесів і апаратів харчових виробництв; кафедра технології хлібопекарських і кондитерських виробів